Radical Knowledge Management: Using Lessons Learned From Artists to Create Sustainable Workplaces - Barnes, Stephanie (Frontiers in Artificial Intelligence, 2021)
This paper weaves together research that has been published over the last 20 years and creates a narrative about how we can change our organisations so that they are fit-for-purpose in the 21st century. Using knowledge management as the starting point and asking the question, how do we move forward in a sustainable, wholistic way to create organisations that are healthy and balanced among social, environmental and financial performance (triple bottom line). This new brand form of knowledge management is called, Radical knowledge management (Radical KM).